1997
DOI: 10.1016/s0167-2789(97)00007-9
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic principle: An experimental test

Abstract: The chaotic hypothesis discussed in Gallavotti and Cohen (1995) is tested experimentally in a simple conduction model. Besides a confirmation of the hypothesis predictions the results suggest the validity of the hypothesis in the much wider context in which, as the forcing strength grows, the attractor ceases to be an Anosov system and becomes an Axiom A attractor. A first text of the new predictions is also attempted

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
176
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(189 citation statements)
references
References 18 publications
9
176
4
Order By: Relevance
“…For this system, the Lyapunov exponents are known to be paired [25,31,32] like in Hamiltonian systems and the average of each pair is a constant equal to σ + /2N d. For E = 5, each pair is composed of a negative and a positive exponent. This means that the attractive set is dense in phase space [10,30] and the chaotic hypothesis is expected to apply to the system yielding a slope X = 1 in the fluctuation relation, as confirmed by our numerical data. The same happens up to E ∼ 20.…”
Section: Numerical Simulation Of Model Isupporting
confidence: 81%
See 3 more Smart Citations
“…For this system, the Lyapunov exponents are known to be paired [25,31,32] like in Hamiltonian systems and the average of each pair is a constant equal to σ + /2N d. For E = 5, each pair is composed of a negative and a positive exponent. This means that the attractive set is dense in phase space [10,30] and the chaotic hypothesis is expected to apply to the system yielding a slope X = 1 in the fluctuation relation, as confirmed by our numerical data. The same happens up to E ∼ 20.…”
Section: Numerical Simulation Of Model Isupporting
confidence: 81%
“…32, is due to the asymmetry of the distribution π τ (p) around the average value p = 1; consequently, it is proportional, at leading order in τ −1 , to ζ (3) ∞ which is indeed a measure of the asymmetry of ζ ∞ (p) around p = 1. This shift would be absent in the case of a symmetric distribution (e.g., a Gaussian) and for this reason it was not observed in previous experiments [6,10,11,15].…”
Section: Remarksmentioning
confidence: 72%
See 2 more Smart Citations
“…Gallavotti then showed that, close to equilibrium (σ + → 0), the FR implies the usual Fluctuation-Dissipation Relation (FDR) [3]. In the recent past, the FR has been tested under a wide class of different conditions, and is now believed to be a very general relation for chaotic systems [4,5,6,7]; recently, it has been also tested in some experiments [8].…”
mentioning
confidence: 99%